Indole-3-Pyruvic Acid, an Aryl Hydrocarbon Receptor Activator, Suppresses Experimental Colitis in Mice - Aoki, Reiji; Aoki-Yoshida, Ayako; Suzuki, Chise; Takayama, Yoshiharu (The Journal of immunology (1950), 2018)
Aryl hydrocarbon receptor (AHR) agonists are promising immunomodulators that potentially maintain immune tolerance. In this study, we examined the ability of indole-3-pyruvic acid (IPA), a major precursor of microbiota-derived AHR agonists and a proagonist of AHR, to activate AHR. The anti-inflammatory effects of IPA were also evaluated in a mouse model of colitis in comparison with other aromatic pyruvic acids (phenylpyruvic acid and 4-hydroxyphenylpyruvic acid). Among them, IPA showed the strongest ability to activate AHR in vitro and in vivo, and only IPA improved chronic inflammation in an experimental colitis model. IPA attenuated the expression of genes encoding Th1 cytokines and enhanced Il-10 gene expression in the colon. Oral administration of IPA decreased the frequency of IFN-γ+ IL-10− CD4+ T cells and increased that of IFN-γ− IL-10+ CD4+ T cells in the colon lamina propria in a T cell–mediated colitis model. IPA directly promoted the differentiation of type 1 regulatory T cells in vitro. Furthermore, IPA administration attenuated the ability of dendritic cells (DCs) in the mesenteric lymph nodes (MLN) to induce IFN-γ–producing T cells, increased the frequency of CD103+ CD11b− DCs, and decreased the frequency of CD103− CD11b+ DCs in the MLN. Adoptive transfer of MLN CD103+ CD11b− DCs significantly improved the severity of colon inflammation. Treatment with an AHR antagonist inhibited IPA-induced differentiation of type 1 regulatory T cells and the IPA-induced increase in CD103+ CD11b− DCs and attenuated the anti-inflammatory effect of IPA. These findings suggest that IPA potently prevents chronic inflammation in the colon by activating AHR.